Estudo de metodologias e materiais para barreira reativa permeável (BRP) - Ikuta, Leticia Ayumi (Universidade Federal de São Carlos, 2020)
Due to increasing environmental contamination by human activity, interventions are necessary to minimize damage in soil, aquifers and rivers, either preventing or hindering the dissemination of contaminants in the environment. One of the methods used to help to contain these harmful substances is Permeable Reactive Barrier (PRB), which can be constituted by different materials. Many of them from recycling such as rice husk charcoal. This study aimed to gather research data on PBR, as well as its applicability, and therewith the author discussed the different types of materials, their applicability and overall potential of this technology. From twenty four selected researches, sixteen submitted diverse reactive materials laboratorial results of which seven were studding for hydrocarbons retention, seven for heavy metals retention and two for nitrogen retention. The experimental difficulties and their authors' suggestions were indicated for the continuation of the research in order to obtain a material and a suitable method for field application. It is interesting to observe that the other eight studies presented PRB applications in the environment, and five of them used only metal as a reactive material, even with the diversity in the materials that had been studied until then. This research proved that PRBs, in general, have favorable results for their usage, decreasing concentration of the contaminants proposed for their execution. Also could be verified PRBs diverse function when explore the materials, its applicabilities and their adequation in shapes and function, however, investment is still needed to continue the work, as well as incentives to have more field application and generate more thorough results of a technology with so much potential.
Study of permeable reactive barriers methodologies and materials
Keywords: contaminação; aquíferos; barreira reativa permeável; materiais; laboratorial; contamination; aquifers; permeable reactive barrier; materials; laboratorial; field; ENGENHARIAS::ENGENHARIA CIVIL::GEOTECNICA